Sensitive detection of NO2 with cavity enhanced spectroscopy - Wojtas, Jacek; Czyżewski, Adam; Stacewicz, Tadeusz; Bielecki, Zbigniew (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
We present an experiment with nitrogen dioxide (NO2) detection with the use of cavity enhanced spectroscopy. The pulsed blue diode laser working at 414 nm as a light source was applied. The cavity was composed of two mirrrors with the reflectivity of R = 0.99992. The off-axis adjustment of the resonator was used. The absorbing gas concentration was determined by the measurement of the decay time of the light pulse trapped in the cavity. The detection limit better than 1 ppb was obtained.
Optica Applicata, Vol. 36, 2006, nr 4, s. 461-467
Keywords: optyka; absorption spectroscopy; optical cavity; gas detector